8. BUDGET EVALUATION AS A BASIS FOR IMPROVING BUDGET QUALITY - Cherry Jelita Saugi; Rita Kusuma Astuti; Pascalis Danny Kristi Wibowo; Nur Priyanto; Suroso; Anwar Hendro; Tutidikatama; Firmansyah (Jurnal TNI Angkatan Udara, 2026)
This study aims to analyze the role of budget evaluation as a basis for improvingbudgeting quality in public sector organizations. The study applies a qualitative approach usinga literature review method covering 15 scientific articles on budget evaluation, performancebased budgeting, budget effectiveness and efficiency, accountability, internal control systems,human resource quality, and the use of budgeting information systems. The data were analyzedthrough content and thematic analysis involving identification, reduction, coding, thematicclassification, and interpretation. The findings indicate that budget evaluation contributes toidentifying discrepancies between plans and realization, assessing the effectiveness andefficiency of fund utilization, improving the clarity of performance indicators, and strengtheningbudget accountability. Budgeting quality is also influenced by human resource competence, dataquality, integration between planning and budgeting, information system utilization, and internalcontrol. The main constraints include inaccurate performance indicators, low budget absorption,limited staff capacity, system disruptions, and weak utilization of evaluation results as feedback.The study concludes that budget evaluation should be conducted periodically, supported byreliable data, and followed up in the preparation of the next budgeting period to produce a moreeffective, efficient, measurable, transparent, and results-oriented budgeting process.